Master in Art Education at University of Aveiro: research, practice and collaborative partnerships with schools - Oliveira, Rosa Maria (2012)
The Bologna agreement brought new concepts and changes on Higher Education courses in Europe and also in the professional life requirements. From now on Art teachers must have a Master in Education in Arts (Visual Arts, Music, etc) for teaching at the different issues and levels of teaching. The new art teachers graduated by University of Aveiro have to attend a year of lectures, develop projects at University and have a second year of practice teaching at a secondary or a basic school involved in collaborative partnership with University of Aveiro. The practice, research and strategies as well as the different intervention activities, which take place during the process both at school and the community, are developed in close cooperation between the University and the schools involved in order to promote the enhancement of the educational process. The work developed is presented in an individual reflective portfolio and a Final Report that is presented in a public session before a Professor’s Committee. This work shall exhibit the activities, innovative proposals, relevant contributes and professional practices, that took place during the second year of the course and strongly contribute for the final evaluation.